Reproductive performance of female Nile tilapia Oreochromis niloticus L. in South Kivu (DR Congo): comparison of two strains differing in origin and history of domestication (International Journal of Scientific Research and Management (IJSRM), 2019)
This study was conducted to evaluate the reproductive performance of females of Oreochromis niloticus originating from a strain of distant origin and extensively exploited in fish farming (Nyakabera strain) and a local strain recently removed from the natural environment (Lac Kivu strain). The experiment was carried out in triplicate with fry of 4.9 to 6.3 g placed in earthen ponds for a period of 6 months, at the Nyakabera fish station in South Kivu, Democratic Republic of Congo. The comparison of the two strains focused on the size of the first sexual maturity, gonado-somatic ratio, fecundity, egg diameter and condition factor. The results showed that under similar managed rearing conditions, the Nyakabera strain reaches sexual maturity earlier and is characterized by a higher gonado-somatic ratio and higher relative fertility, but a worse condition compared to the Lac Kivu strain. These differences, which indicate a better reproductive success of the Nyakabera strain, are related to the origin and the history of domestication, which are just as different from these two strains.